Recycling method of novel lithium ion sieve adsorbent material, obtained adsorbent material and application

By recycling and regeneration of the new lithium ion sieve adsorbent material, the problems of low adsorption capacity and poor selectivity in the brine extraction process are solved, and the adsorption performance recovery and multiple recycling of materials are achieved, reducing the generation of waste.

CN119746802APending Publication Date: 2025-04-04NINGBO GRAPHENE INNOVATION CENT CO LTD

Patent Information

Application Number
CN202510035462.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing aluminum-based adsorbent materials have low adsorption capacity and poor selectivity during the brine lithium extraction process, which limits the efficiency and production capacity of brine lithium extraction, and fails to realize the recycling of adsorbent materials.

Method used

Using a new type of lithium ion sieve adsorbent material recovery and regeneration method, by calculating the loss of metal elements M1 and Li in the waste adsorbent material after adsorption of lithium, using corresponding metal-containing compounds to mix them uniformly with the waste adsorbent material, and high-temperature heat treatment is performed to restore the adsorption performance.

Benefits of technology

It realizes the recovery of adsorption performance, has a high recovery rate of adsorption performance, good stability of the material, can be recycled multiple times, reduces the generation of waste, and meets the requirements of green resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746802A_ABST
    Figure CN119746802A_ABST
Patent Text Reader

Abstract

The invention relates to a method for recycling a novel lithium ion sieve adsorbent material, an obtained adsorbent material and application, and the method comprises the following steps: firstly, preparing an adsorbent material with a molecular formula of M1y (LixM21-x) O2, M1 being selected from non-lithium alkali metal elements Na and / or K; 0 lt; y is less than or equal to 1, M2 is selected from at least one of transition metal elements Fe, Co, Ni and Mn, and Li and the transition metal element M2 occupy a lattice position, 0 lt; xlt; 0.5, weighing the waste adsorption material after long-term lithium adsorption; the loss amount of the metal elements M1 and Li in the waste adsorption material is calculated according to the ICP element content test result, and the loss amount of the metal elements M1 and Li in the material is calculated according to the ICP element content test result; according to the loss amount, a corresponding compound containing metal elements is adopted as a raw material and is uniformly mixed with the waste adsorption material, then heat treatment is performed, and the obtained material is the regenerated adsorbent material; the method has the advantages that the adsorption performance of the material can be recovered, so that the material can be reused, the recovery rate of the adsorption performance is high, and the stability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium extraction from brine, and in particular to a method for recovering and regenerating a novel lithium ion sieve adsorbent material, the adsorbent material obtained, and its application. Background Art

[0002] Due to the demand for sustainable development of the social environment, electric vehicles and new energy technologies have been widely developed. These developments are largely based on the development and maturity of lithium-ion battery technology. The booming electric vehicle industry and the emerging energy storage industry have intensified the demand for lithium-ion batteries and lithium resources. The mining of lithium resources requires the development of various lithium extraction technologies. Traditional lithium resource production, which mainly relies on lithium-rich hard rock mines and salt lake brines, will bring about a large amount of energy consumption, greenhouse gas emissions, groundwater consumption, geological environmental interference, etc., causing environmental problems and supply chain problems.

[0003] Compared with lithium-containing ores, the lithium resources in salt lake brine account for about 60% of the world's lithium resources, and the cost of lithium extraction is lower, making it the main source of lithium resources. In terms of lithium extraction technology from brine, the adsorption method is widely used due to its good ion selectivity, environmental friendliness, and high recycling rate. The core technology of the adsorption method is the adsorbent material, and the only commercial aluminum-based adsorbent material currently available has problems such as low adsorption capacity and poor selectivity, which greatly limits the efficiency and production capacity of lithium extraction from brine.

[0004] In the patent document with patent publication number: CN 117101599 B, a new lithium adsorption material is provided, and its molecular structure is as follows: M1 y (Li x M2 1-x )O2, due to the characteristics of high adsorption capacity, high selectivity, and environmental friendliness, the material has broad application prospects in the extraction of lithium from various lithium-containing brines such as salt lake brine, mine brine, geothermal brine, sedimentary water, oilfield water, and lithium-containing wastewater generated in the process of lithium-ion battery recovery; however, this adsorption material with such advantages has not achieved recycling in its subsequent applications after the adsorption of lithium. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present application provides a method for recovering and regenerating a novel lithium ion sieve adsorbent material that can realize the recovery of the adsorption performance of the material, thereby allowing the material to be reused, and has a high recovery rate of adsorption performance and good stability.

[0006] In order to solve the above technical problems, the technical solution adopted in this application is: a new method for recycling and regenerating lithium ion sieve adsorbent materials, the steps of which include:

[0007] (1) First, the molecular formula is M1y (Li x M2 1-x )O2 novel lithium-ion adsorbent material, wherein M1 is selected from non-lithium alkali metal elements Na and / or K; 0 < y ≤ 1, M2 is selected from at least one of transition metal elements Fe, Co, Ni, and Mn, Li and transition metal element M2 together occupy one lattice position, 0 < x < 0.5, and the waste adsorbent material after long-term lithium adsorption is weighed;

[0008] (2) Calculate the loss amounts of metal elements M1 and Li in the waste adsorbent material after long-term lithium adsorption. Specifically, according to the results of ICP element content testing, calculate the loss amounts of metal elements M1 and Li in the material;

[0009] (3) According to the loss amounts, use the corresponding metal element-containing compounds as raw materials, uniformly mix them with the waste adsorbent material, and then perform heat treatment. The obtained material is the regenerated adsorbent material.

[0010] Further, the waste adsorbent material after long-term lithium adsorption described in step (1) is: the adsorption performance of the waste adsorbent material whose adsorption performance is lower than 50% compared with the original adsorbent material with the molecular formula M1 y (Li x M2 1-x )O2.

[0011] Further, the corresponding metal element-containing compounds include M1 element-containing compounds, and the M1 element-containing compounds include at least one of oxides, carbonates, oxalates, acetates, hydroxides of sodium, potassium, rubidium, cesium, etc.

[0012] Further, the corresponding metal element-containing compounds include Li element-containing compounds, and the Li element-containing compounds include at least one of lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, lithium hydroxide.

[0013] Further, the methods of uniform mixing include but are not limited to manual grinding, ball milling, and sand milling.

[0014] Further, the heat treatment temperature after uniform mixing is between 100 - 950 °C, and the heat treatment time is between 10 min - 48 h.

[0015] Even further, the heat treatment temperature is 500 - 750 °C, and the heat treatment time is 0.5 - 6 hours.

[0016] This application also provides a novel lithium-ion sieve adsorbent material, which is a regenerated adsorbent material prepared by the recycling and regeneration method of the novel lithium-ion sieve adsorbent material described above.

[0017] The present application also provides an application of an adsorbent material obtained by the above-mentioned novel lithium ion sieve adsorbent material recovery and regeneration method in lithium extraction from brine.

[0018] Advantages and beneficial effects of the present invention:

[0019] 1. This application is directed to the specific new lithium ion adsorbent material M1 in the publication number CN117101599 B y (Li x M2 1-x )O2, develop a regeneration process for the adsorbent material, the regeneration process can calculate the specific loss of metal elements M1 and Li lost by the above-mentioned adsorbent used for multiple adsorptions, and more accurately replenish the lost metal elements, and then the regenerated adsorbent material obtained by high-temperature calcination has almost no difference in performance from the original material without lithium adsorption, even if the regenerated adsorbent material obtained by this regeneration process is recycled for lithium adsorption for multiple cycles, the adsorption performance of the regenerated adsorbent material will not be lost or attenuated, and the adsorption performance of the original adsorbent material before adsorption can still be maintained.

[0020] 2. This regeneration process of the present application is aimed at the adsorption performance of the original molecular formula M1 y (Li x M2 1-x ) The adsorption performance of O2 adsorption materials drops to less than 50%, and then a regeneration process is carried out; when the adsorption performance of the adsorption material drops to less than 50% of the adsorption performance of the original adsorption material, it can basically only be treated as a waste material or a retired adsorption material. The present application creatively regenerates such waste materials with low adsorption performance, and can also make the adsorption material obtained in each regeneration process almost completely restore to the adsorption performance of the original adsorption material. Even in multiple and long-term cyclic adsorption and regeneration processes, its adsorption performance is almost not lost, thereby reducing the generation of waste and meeting the requirements of green resource circulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the initial XRD spectrum of the original adsorption material without lithium adsorption in Example 1.

[0022] Figure 2 XRD pattern of the spent adsorbent material obtained after long-term lithium adsorption.

[0023] Figure 3 This is the XRD spectrum of the adsorbent material obtained after regeneration according to the method of Example 1. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments and the accompanying drawings. Obviously, the described embodiments are only preferred embodiments, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention;

[0025] Example 1

[0026] Weigh the retired adsorbent material (i.e., the waste adsorbent material after lithium adsorption) for XRD test and ICP test; the XRD pattern of the retired material is shown in Figure 2 , and Figure 1 is completely different from the initial XRD pattern of the adsorbent material without lithium adsorption, indicating that its crystal structure has deviated seriously from the initial structure of the material; then, according to the ICP test results, the percentage contents of M1, Li, and M2 are obtained. Taking the content of M2 as a reference (the absolute content of M2 may often be inaccurate, and it is more reliable to use the relative content here), it is determined that the losses of M1 and Li are 90% and 10% respectively. According to the content of M2, weigh 1 mol of the waste adsorbent material, 0.9y (0 < y ≤ 1) mol of M1OH, and 0.1x (0 ≤ x < 0.5) mol of LiOH, and ball-mill them in a ball mill at a rotation speed of 300 rpm for 5 hours. After mixing them evenly, transfer them to a muffle furnace, heat them to 750 °C at a rate of 5 °C per minute, keep them warm for 8 hours, and then cool them naturally to room temperature to obtain the regenerated adsorbent material.

[0027] The regenerated adsorbent material is subjected to X-ray diffraction detection, and the results are shown in Figure 3 . According to this Figure 3 , it can be seen that this pattern is basically the same as the original pattern of the material Figure 1 , indicating that the regenerated adsorbent material has been restored to the initial material structure, and its structural formula is M1 y (Li x M2 1-x )O2.

[0028] The above-mentioned waste adsorbent material after lithium adsorption or the retired adsorbent material is specifically an adsorbent material whose adsorption efficiency is reduced to less than 50% of the adsorption efficiency of the original adsorbent material after being recycled by the following method. The sources of the waste adsorbent materials in the subsequent examples are similar: Prepare a sufficient amount of qualified lithium-containing solution or other lithium-containing solution to be adsorbed, use a new type of lithium ion adsorbent material (CN 117101599 B) to adsorb the brine; after sufficient adsorption, rinse it with clean water to wash away the residual brine on the surface of the material; elute the lithium adsorption material with acid solution; after sufficient elution, rinse it with clean water to wash away the residual acid solution on the surface of the material; perform alkali treatment on the material to restore its partial adsorption performance.

[0029] Specifically, a qualified lithium-containing solution with a Li concentration of 0.8 g / L, a Na concentration of 0.3 g / L, a K concentration of 0.8 g / L, and a Mg concentration of 1.6 g / L can be used here. Then, 160 ml of its structural formula M1 is added to a 200 ml single column y (Li x M2 1-x )O2 (CN117101599B) original novel adsorbent material. In an environment at room temperature of 25 °C, the qualified solution is passed at a flow rate of 8 bv / h for 6 h to allow sufficient adsorption. Then, after passing clear water at 15 bv / h for 1 h, 0.1 M hydrochloric acid is passed at 12 bv / h for 12 h to fully desorb and remove lithium. After passing clear water at 15 bv / h for 1 h again, sodium hydroxide lye is passed. The total concentration of cations (Na + ) in the sodium hydroxide lye is 10 M, the flow rate is set at 12 bv / L, and the passing time is 8 h. After passing clear water at 15 bv / h for 1 h again, the qualified solution is passed with the same parameters, and the above adsorption and regeneration operations are repeated; it can be recycled about 2000 times. At this time, the adsorption efficiency of the adsorbent material is reduced to less than 50% of the original. This material is used as the waste adsorbent material after adsorbing lithium, and then the XRD test and ICP test are carried out using the method described in the first paragraph of Example 1 above to calculate and determine the loss of M1 and Li, and the elements are supplemented, mixed, and sintered to obtain the regenerated adsorbent material.

[0030] Example 2

[0031] Using different raw materials, continue to recycle and regenerate the retired adsorbent material in Example 1. Weigh 1 mol of the waste adsorbent material, 0.45y (0 < y ≤ 1) mol of M12CO3, and 0.025x (0 ≤ x < 0.5) mol of Li2CO3. (0.45 and 0.025 in this example are half of those in Example 1 because the carbonate M12CO3 and Li2CO3 used in this example are twice the content of M1OH and LiOH in Example 1; the subsequent examples are based on a similar principle) Ball mill in a ball mill at a rotational speed of 300 rpm for 5 hours. After mixing them evenly, transfer them to a muffle furnace and heat them to 700 °C at a rate of 5 °C per minute, hold for 8 hours, and then naturally cool to room temperature to obtain the regenerated adsorbent material, whose structural formula is M1 y (Li x M2 1-x )O2.

[0032] Example 3

[0033] Using different raw materials, continue to recycle and regenerate the retired adsorbent material in Example 1; Weigh 1 mol of waste adsorbent material, 0.45y (0 < y ≤ 1) mol of M12CO3, and 0.1x (0 ≤ x < 0.5) mol of LiOH, ball mill in a ball mill at a rotation speed of 300 rpm for 5 hours. After mixing them evenly, transfer them to a muffle furnace, heat up to 750 °C at a rate of 5 °C per minute, keep warm for 12 hours, and naturally cool to room temperature to obtain the regenerated adsorbent material, whose structural formula is M1 y (Li x M2 1-x )O2.

[0034] Example 4

[0035] Using different raw materials, continue to recycle and regenerate the retired adsorbent material in Example 1. Weigh 1 mol of waste adsorbent material, 0.45y (0 < y ≤ 1) mol of M12O, and 0.1x (0 ≤ x < 0.5) mol of lithium acetate, ball mill in a ball mill at a rotation speed of 300 rpm for 5 hours. After mixing them evenly, transfer them to a muffle furnace, heat up to 680 °C at a rate of 5 °C per minute, keep warm for 8 hours, and naturally cool to room temperature to obtain the regenerated adsorbent material, whose structural formula is M1 y (Li x M2 1-x )O2.

[0036] From the above examples and test results, it can be seen that this method of the present application for this specific new lithium-ion adsorbent material M1 in CN 117101599 B y (Li x M2 1-x )O2, where M1 is selected from non-lithium alkali metal elements Na and / or K; 0 < y ≤ 1, M2 is selected from at least one of transition metal elements Fe, Co, Ni, and Mn, Li and transition metal element M2 together occupy one lattice position, 0 < x < 0.5; A method for regenerating the waste adsorbent material obtained after its long-term lithium adsorption, the adsorbent material can be restored to the lithium adsorption performance of the initial adsorbent material, and this regeneration method is achieved through high-temperature treatment, and the obtained adsorbent material and the original new lithium-ion adsorbent material M1 that has not adsorbed lithium y (Li x M2 1-x)O2 has basically no difference in performance, and a complete regeneration effect is achieved, so that this new lithium ion adsorbent material can be cyclically used to extract lithium, thereby effectively saving the loss of the adsorbent material, allowing it to be recycled and reducing costs; and the regeneration process of the present application is simple to operate and is suitable for industrial operation, which can enable the new adsorbent material to have the ability to be recycled for a long time and has a good application prospect.

Claims

1. A novel method for recycling and regenerating lithium ion sieve adsorbent material, characterized in that: The steps of the method include: (1) First, the molecular formula is M1 y (Li x M2 1-x )O2 novel lithium-ion adsorbent material, where M1 is selected from non-lithium alkali metal elements Na and / or K; 0 < y ≤ 1, M2 is selected from at least one of transition metal elements Fe, Co, Ni, and Mn, Li and transition metal element M2 together occupy one lattice position, 0 < x < 0.5, and the discarded adsorbent material after its long-term lithium adsorption is weighed; (2) calculating the loss of metal elements M1 and Li in the waste adsorption material after long-term adsorption of lithium; specifically, calculating the loss of metal elements M1 and Li in the material according to the results of the ICP element content test; (3) According to the loss amount, the corresponding metal element-containing compound is used as raw material, uniformly mixed with the waste adsorbent material, and then heat-treated. The obtained material is the regenerated adsorbent material.

2. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 1, characterized in that: The waste adsorption material after long-term lithium adsorption in step (1) has an adsorption performance higher than that of the original molecular formula M1 y (Li x M2 1-x )O2 adsorbent material, and waste adsorbent material whose adsorption performance has dropped to less than 50%.

3. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 1, characterized in that: The corresponding metal element-containing compound includes a compound containing the M1 element, and the compound containing the M1 element includes but is not limited to at least one of oxides, carbonates, oxalates, acetates, and hydroxides of sodium, potassium, rubidium, and cesium.

4. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 1, characterized in that: The corresponding metal element-containing compound includes a Li-containing compound, and the Li-containing compound includes but is not limited to at least one of lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, and lithium hydroxide.

5. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 1, characterized in that: The uniform mixing method includes but is not limited to manual grinding, ball milling, and sand milling.

6. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 1, characterized in that: The temperature of the heat treatment after the uniform mixing is between 100-950° C., and the time of the heat treatment is between 10 minutes and 48 hours.

7. The method for recycling and regenerating the novel lithium ion sieve adsorbent material according to claim 6, characterized in that: The heat treatment temperature is 500-750° C., and the heat treatment time is 0.5-6 hours.

8. A novel lithium ion sieve adsorbent material, characterized in that: The adsorbent material is prepared according to the recovery and regeneration method of the novel lithium ion sieve adsorbent material according to any one of claims 1 to 7.

9. The lithium ion sieve adsorbent material according to claim 8, characterized in that: The adsorbent material is used for extracting lithium from brine.

Citation Information

Patent Citations

  • A lithium ion sieve adsorbent material and its preparation method and application

    CN117101599B

Cited By

  • Recovery and regeneration method of invalid titanium adsorbent

    CN121198273A